ECONOMIC AND SOCIAL DEVELOPMENT OF POST-SOVIET AZERBAIJAN: THE TENDENCIES, THE DYNAMIC AND THE RESULTS - KARAMOURZOV, R.B. (Kavkazologiya, 2020)
The paper deals with the dynamics of some socio-economic indicators of Azerbaijan for more than two and a half decades. Thorough description of the indicators used for the analysis is provided. The relative dynamics of both total and per capita GDP is investigated. The conclusions on structural changes of the GDP since the collapse of the USSR are drawn. The number and the structure of Azerbaijan’s labor resources are analyzed. Some aspects of labor emigration are highlighted. An overview of the Human Development Index and its basic components is made. Data on the changes of the Sustainable Development Goals Index is provided. Certain indicators of Azerbaijan are compared to those of some other countries. The analysis revealed that by the end of the 2010s total and per capita GDP of Azerbaijan exceeded the 1990 level, respectively, 2.5 and 1.8 times. The population increased by 40%. The share of industry in GDP has grown more than 1,7 times (exclusively due to its extractive industries). The share of agriculture in GDP decreased from 26 to 5%, while the share of the services sector was at the level of 1990. By 2019, the share of persons employed in agriculture fell to 36%, the share of people employed in services increased to about 50% and the share of those employed in industry increased to 14-15%. From 1995 to 2018 the score of the Human Development Index of Azerbaijan increased by almost 25%. The positions of Azerbaijan in world SDG index ranking haven’t changed significantly.